Building brand credibility to increase consumer purchase intention: The role of influencer emotional attachment - Fatik Rahayu; Raymond Siregar; Kahti Ramadhia Risde; Dyahayu Amanda Nurulita; Faiq Raihan Wijarnako; Khansa Fara Wijarnako; Luo Ying (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2024)
Influencer marketing is becoming more common in online shopping on social media, leading influencers to focus on improving the quality and uniqueness of their content. Previous studies have mainly focused on identifying influencer traits that affect the effectiveness of influencer marketing. This study aims to fill the gap by complementing and expanding this research using the meaning transfer model to investigate the role of emotional attachment in building brand credibility and increasing consumer purchase intention in Indonesia. Data from 268 participants were collected through questionnaires, and structural equation modeling was used for analysis. The results indicated that interactivity had a positive impact on influencer authenticity. Additionally, authenticity influences emotional attachment, affecting brand credibility and purchase intention. Based on these results, influencers should strive to be professional, honest, and objective and understand their followers' characteristics to enhance emotional attachment.